Coloring of recycled rubber and plastic tiles and their opto-thermal response - Sanchez Amono, María Paz (2025)
Energy efficiency consists of achieving lower energy consumption compared to the same benefit The different amount of solar radiation that is reflected or absorbed is due to the surface color. The tiles developed in this research are black, as they have rubber particles in their composition, which contain carbon black. Dark colors have a higher solar absorptivity, therefore, the alternative of coloring the tiles with light colors was analyzed, to reduce the absorption of solar radiation. The objective is to evaluate different technical possibilities for laying tiles from the incorporation of pigments, and to determine the energy efficiency. For manufacturing, colored oxides, masterbatch, rubber and polyethylene were incorporated. Experiments were carried out varying their dosages and for the determination of the thermo-physical behavior of the tiles, optical properties (albedo and emissivity) and surface temperature of 2 sample units were tested -one tile colored in green and one in black-. The group with the best results was number 3, where black rubber, green polyethylene and masterbatch were mixed. When comparing the thermo-physical performance of recycled green tiles in relation to black tiles, a more efficient behavior was observed in green tiles. Increases in the albedo level of 11% and decreases in surface temperature greater than 8 ° C were recorded. Energy efficiency consists of achieving lower energy consumption compared to the same benefit The different amount of solar radiation that is reflected or absorbed is due to the surface color. The tiles developed in this research are black, as they have rubber particles in their composition, which contain carbon black. Dark colors have a higher solar absorptivity, therefore, the alternative of coloring the tiles with light colors was analyzed, to reduce the absorption of solar radiation. The objective is to evaluate different technical possibilities for laying tiles from the incorporation of pigments, and to determine the energy efficiency. For manufacturing, colored oxides, masterbatch, rubber and polyethylene were incorporated. Experiments were carried out varying their dosages and for the determination of the thermo-physical behavior of the tiles, optical properties (albedo and emissivity) and surface temperature of 2 sample units were tested -one tile colored in green and one in black-. The group with the best results was number 3, where black rubber, green polyethylene and masterbatch were mixed. When comparing the thermo-physical performance of recycled green tiles in relation to black tiles, a more efficient behavior was observed in green tiles. Increases in the albedo level of 11% and decreases in surface temperature greater than 8 ° C were recorded. Energy efficiency consists of achieving lower energy consumption compared to the same benefit The different amount of solar radiation that is reflected or absorbed is due to the surface color. The tiles developed in this research are black, as they have rubber particles in their composition, which contain carbon black. Dark colors have a higher solar absorptivity, therefore, the alternative of coloring the tiles with light colors was analyzed, to reduce the absorption of solar radiation. The objective is to evaluate different technical possibilities for laying tiles from the incorporation of pigments, and to determine the energy efficiency. For manufacturing, colored oxides, masterbatch, rubber and polyethylene were incorporated. Experiments were carried out varying their dosages and for the determination of the thermo-physical behavior of the tiles, optical properties (albedo and emissivity) and surface temperature of 2 sample units were tested -one tile colored in green and one in black-. The group with the best results was number 3, where black rubber, green polyethylene and masterbatch were mixed. When comparing the thermo-physical performance of recycled green tiles in relation to black tiles, a more efficient behavior was observed in green tiles. Increases in the albedo level of 11% and decreases in surface temperature greater than 8 ° C were recorded.